2016
DOI: 10.1371/journal.pone.0165932
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Depth Judgments on Smoothly Curved Surfaces

Abstract: Binocular disparity is an important cue to depth, allowing us to make very fine discriminations of the relative depth of objects. In complex scenes, this sensitivity depends on the particular shape and layout of the objects viewed. For example, judgments of the relative depths of points on a smoothly curved surface are less accurate than those for points in empty space. It has been argued that this occurs because depth relationships are represented accurately only within a local spatial area. A consequence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Recently, researchers have shown that the perception of quantitative depth in binocular stimuli depends upon surrounding disparity information, with the presence of continuous gradations in disparity resulting in a reduction in perceived depth (Cammack & Harris, 2016;Deas & Wilcox, 2014, 2015Hornsey, Hibbard, & Scarfe, 2016). These recent findings are consistent with much earlier results, which showed that disparity discrimination thresholds are increased for pairs of vertical lines when intervening horizontal lines create a closed figure (McKee, 1983;Mitchison & Westheimer, 1984).…”
Section: Introductionsupporting
confidence: 82%
“…Recently, researchers have shown that the perception of quantitative depth in binocular stimuli depends upon surrounding disparity information, with the presence of continuous gradations in disparity resulting in a reduction in perceived depth (Cammack & Harris, 2016;Deas & Wilcox, 2014, 2015Hornsey, Hibbard, & Scarfe, 2016). These recent findings are consistent with much earlier results, which showed that disparity discrimination thresholds are increased for pairs of vertical lines when intervening horizontal lines create a closed figure (McKee, 1983;Mitchison & Westheimer, 1984).…”
Section: Introductionsupporting
confidence: 82%
“…An alternative possibility to these zero-crossing dependent processes can be found in the work of Glennerster and colleagues (Glennerster & McKee, 1999Petrov & Glennerster, 2004. These authors have argued for mechanisms that compare the disparity of isolated points to a measured, or inferred, reference plane (see also Hornsey et al, 2016). Such mechanisms could help to account for some of the slant-dependent effects found in Experiment 2 if the reference surface…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Goutcher and colleagues (Goutcher et al, 2018;Goutcher & Hibbard, 2020) have suggested that this stage of processing plays a critical role in producing observed biases in the perceived depth of continuous and discontinuous surfaces (Cammack & Harris, 2016, Goutcher et al, 2018 and in the masking of disparity-defined surface structures by random disparity masking stimuli (Goutcher & Hibbard, 2020). Mechanisms selective for relative disparity may also be involved in other stereoacuity biases, including observed effects of slanted or curved reference planes (Glennerster & McKee, 1999Hornsey, Hibbard & Scarfe, 2016;Petrov & Glennerster, 2004.…”
Section: Introductionmentioning
confidence: 99%